2007
DOI: 10.1111/j.1439-0396.2007.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineral balance in horses fed two supplemental silicon sources

Abstract: Numerous studies suggest that silicon (Si) supplementation is beneficial for mineral metabolism and bone health. Mineral balance studies have not been performed in horses to determine how these supplements affect absorption of other minerals. The purpose of these studies was to investigate the effects of two different Si supplements on mineral absorption and retention in horses. Eight geldings were randomly placed in one of two groups: control (CO) or supplemental Si, which was provided by one of two supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
(51 reference statements)
0
15
1
1
Order By: Relevance
“…In this paper, we critically review the most recent findings on biological effects of Si and ortho-silicic acid on animals and human beings. Moreover, we propose that previously observed positive biological effects of various colloidal silicic acids (various hydrated silica gels) as well as some zeolites [4-6], e.g. zeolite A (Figure 2) and clinoptilolite (Figure 3), might be, at least partially, ascribed to the ortho-silicic acid-releasing property.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In this paper, we critically review the most recent findings on biological effects of Si and ortho-silicic acid on animals and human beings. Moreover, we propose that previously observed positive biological effects of various colloidal silicic acids (various hydrated silica gels) as well as some zeolites [4-6], e.g. zeolite A (Figure 2) and clinoptilolite (Figure 3), might be, at least partially, ascribed to the ortho-silicic acid-releasing property.…”
Section: Introductionmentioning
confidence: 73%
“…Animal studies have also shown the possibility of zeolite A (sodium aluminosilicate) as a viable source of silicon [4,6,114]. The latter is one of known zeolites that breaks down into bioavailable ortho-silicic acid (H 4 SiO 4 ) in the digestive system.…”
Section: Zeolites As a Source Of Ortho-silicic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their prolonged use or misuse pose the risk for developing cross-resistance and multiple-antibiotic resistance in bacterial strains pathogenic for both animals and humans which has been strongly related to the therapeutic, metaphylactic or prophylactic administration of antibiotics in human and veterinary medicine (15). The dietary strategy of using zeolites in animal studies have shown the possibility of zeolite A as a viable source of silicon for dogs and horses (42,43,50) due to its property to breaks down into bioavailable OSA, (H 4 SiO 4 ) in the digestive system (32). Thus, it provides additional source of silicon to the organism resulting in decreased skeleton injury rates and better training performances in young racing horses (47).…”
Section: Companion Animals and Horsesmentioning
confidence: 99%
“…Furthermore, zeolites have been successfully utilized for wound and surgical incision healing (31), including skin burns (41), for hemorrhage control (32) and dental treatment (26). However, recently it was recognized that previously observed positive biological effects of various colloidal silicic acids (various hydrated silica gels) as well as of some zeolites, such as zeolite A and CPL might be partially ascribed to their ortho-silicic acid (OSA)-releasing property (26,32,42,43). Namely, numerous biologically active silicon compounds such as some types of zeolites, particularly CPL, are major natural sources of the OSA as documented so far.…”
Section: Introductionmentioning
confidence: 99%